Good Governance dalam Perspektif Perguruan Tinggi Swasta untuk Menghadapi Persaingan - Hariyanto, Simon (Jurnal Widya Manajemen & Akuntansi, 2004)
Every organization has an aim which is either profit oriented or non profit oriented. In other words, organizations deal with the effectiveness of their operation. In order lo achieve their goal, they must handicap a nature, structure and business environment. The process to achieve all organization goals needs several tool. A Good Governance is one of the tolls that takes an important responsibility role to principal and stakeholders. His paper draws six principles based of good governance which measure efficiency and effectiveness of public organization as universities and academic. Moreover, these principles evaluate the organization performance.